The impact of air pollution casts on the infrastructure programme : – some Swedish results. - Hesselborn, Per-Ove (Proceedings from the Annual Transport Conference at Aalborg University, 1997)
The purpose of the paper is to present some Swedish results concerning the importance for infrastructure programmes of internalising air pollution costs. The work that is presented was done by SIKA for a parliamentary commission that was appointed in 1994 with the task to suggest a new transport policy compatible with demands for long run environmental sustainability.